Health care resource use and direct medical costs for patients with schizophrenia in Tianjin, People’s Republic of China - Wu, Jing (Neuropsychiatr Dis Treat, 2015)
OBJECTIVE: Information concerning the treatment costs of schizophrenia is scarce in People’s Republic of China. The aims of this study were to quantify health care resource utilization and to estimate the direct medical costs for patients with schizophrenia in Tianjin, People’s Republic of China. METHODS: Data were obtained from the Tianjin Urban Employee Basic Medical Insurance (UEBMI) database. Adult patients with ≥1 diagnosis of schizophrenia and 12-month continuous enrollment after the first schizophrenia diagnosis between 2008 and 2009 were included. Both schizophrenia-related, psychiatric-related, and all-cause related resource utilization and direct medical costs were estimated. RESULTS: A total of 2,125 patients were included with a mean age of 52.3 years, and 50.7% of the patients were female. The annual mean all-cause costs were $2,863 per patient with psychiatric-related and schizophrenia-related costs accounting for 84.1% and 62.0% respectively. The schizophrenia-related costs for hospitalized patients were eleven times greater than that of patients who were not hospitalized. For schizophrenia-related health services, 60.8% of patients experienced at least one hospitalization with a mean (median) length of stay of 112.1 (71) days and a mean cost of $1,904 per admission; 59.0% of patients experienced at least one outpatient visit with a mean (median) number of visits of 6.2 (4) and a mean cost of $42 per visit during the 12-month follow-up period. Non-medication treatment costs were the most important element (45.7%) of schizophrenia-related costs, followed by laboratory and diagnostic costs (19.9%), medication costs (15.4%), and bed fees (13.3%). CONCLUSION: The costs related to the treatment of patients with schizophrenia were considerable in Tianjin, People’s Republic of China, driven mainly by schizophrenia-related hospitalizations. Efforts focusing on community-based treatment programs and appropriate choice of drug treatment have the potential to reduce the use of inpatient services and may lead to better clinical and economic outcomes in the management of patients with schizophrenia in People’s Republic of China.